Spermidine improves the antioxidant capacity and morphology of intestinal tissues and regulates intestinal microorganisms in Sichuan white geese - Wang, Zelong; Jiang, Dongmei; Wang, Xin; Jiang, Yilong; Sun, Qian; Ling, Weikang; An, Xiaoguang; Ji, Chengweng; Li, Shuo; Qi, Yuxin; Kang, Bo (Frontiers in Microbiology, 2024)
Intestinal health is very important to the health of livestock and poultry, and is even a major determining factor in the performance of livestock and poultry production. Spermidine is a type of polyamine that is commonly found in a variety of foods, and can resist oxidative stress, promote cell proliferation and regulate intestinal flora. In this study, we explored the effects of spermidine on intestinal health under physiological states or oxidative stress conditions by irrigation with spermidine and intraperitoneal injection of 3-Nitropropionic acid (3-NPA) in Sichuan white goose. Our results showed that spermidine could increase the ratio of intestinal villus to crypt and improve intestinal morphology. In addition, spermidine can also reduce malondialdehyde (MDA) accumulation caused by 3-NPA by increasing superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPX) enzyme activity, thus alleviating intestinal damage. Furthermore, spermidine can regulate intestinal digestive enzyme activities and affect intestinal digestion and absorption ability. Spermidine can also promote an increase in intestinal microbial diversity and abundance and alleviate the change of microflora structure caused by 3-NPA. In conclusion, spermidine promotes the production of beneficial intestinal metabolites such as Wikstromol, Alpha-bisabolol and AS 1-5, thus improving the level of intestinal health. Taken together, these results indicate that spermidine can improve intestinal health by improving intestinal morphology, increasing antioxidant capacity and regulating intestinal flora structure.